10=-6-y

Simple and best practice solution for 10=-6-y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10=-6-y equation:


Simplifying
10 = -6 + -1y

Solving
10 = -6 + -1y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add 'y' to each side of the equation.
10 + y = -6 + -1y + y

Combine like terms: -1y + y = 0
10 + y = -6 + 0
10 + y = -6

Add '-10' to each side of the equation.
10 + -10 + y = -6 + -10

Combine like terms: 10 + -10 = 0
0 + y = -6 + -10
y = -6 + -10

Combine like terms: -6 + -10 = -16
y = -16

Simplifying
y = -16

See similar equations:

| 4=5x-15 | | 2+3y=11 | | 4x+2(x-3)=3x+x-12 | | -2a+14=0 | | (80x-52y)-(62x+21y)= | | 4a-6=-14 | | 22=(2)(3.14)r | | 6(c+4)=4c--18 | | -4x-33=4+3(1-8x) | | 5n+9(n-1)=11n-(2n+4) | | 12=x-(-6) | | .05x+.06y=270 | | 5v+2=22 | | 3x+5-2+67=92 | | 1x-0.60=60 | | m+16=3m-8 | | 3x+5-4=2(x+2)+x | | (80x+62y)-(7x+26y)= | | 17-12+X=2X | | (52x+50y)-(-26x+3y)= | | 5x+10=5x+15 | | 15-8v=-1 | | 0=2x^2-x-7 | | 6(X+2)-4=8(X-2)+8 | | -4u-21=-7(u+6) | | 5(2x-1)-4x=11 | | 4x+8-2x=39+1 | | (71x+62y)-(3x+32y)= | | 6(6a-3)=5(7a+1) | | 0.5(6)-4y=1 | | 3(2x+1)5=6(x+1) | | x*(x+6)=84 |

Equations solver categories